Impact of sensorimotor training with whole body vibration platform on balance and functional mobility of an elderly individual after a stroke: case report (Fisioterapia e Pesquisa, 2016)
The incidence of cerebrovascular accident (CVA) increases with aging and can result in sensory and motor changes, which limit functional capacity due to the reduction in balance and mobility. Different resources are being used by physical therapists in their practice to recover balance and mobility, such as sensorimotor training and training with a vibrating platform. The objective of this study was to investigate the effect of a sensorimotor training protocol with vibrating platform on the balance and functional mobility of an older adult with CVA sequela. An older adult, of the female sex, aged 72 years and with CVA sequela participated in this study. The assessment of balance was performed through the Berg Balance Scale (BBS) and the assessment of mobility through the Timed Up and Go Test (TUG). The dependent variables for monitoring were: score obtained through BBS and execution time of TUG. After the initial assessment, the older adult went through a sensorimotor training protocol with a vibration platform, comprised of 10 sessions of 45 minutes. With the final assessment, the results showed an increase in the scores of BBS (initial assessment = 41 points; final assessment = 51 points) and a reduction in the execution time of TUG (initial assessment = 14 seconds; final assessment = 9 seconds) in the older adult with CVA sequela. Based on these results, we can conclude that the proposed training was effective for the improvement of balance and functional mobility of the older adult with CVA sequela.